Systematic placement of some taxa in the family Galumnidae (Acari, Oribatida) - Ermilov, Sergey G.; Bayartogtokh, Badamdorj (Zootaxa, 2015)
Based on the recent ascertaining studies of type specimens, the new systematic placement for one subgenus and three species of oribatid mites of the family Galumnidae (Acari, Oribatida) are proposed, resulting in the following taxonomic proposals: Pergalumna (Bigalumna) Mahunka & Mahunka-Papp, 2009 stat. nov., P. (B.) rimosa (Mahunka & Mahunka-Papp, 2009) comb. nov., Allogalumna quadrimaculata (Mahunka, 1988) comb. nov. and A. brevisetosa (Bayartogtokh & Weigmann, 2005) comb. nov. The initial taxonomic position of the species, Galumna scripta Balogh & Mahunka, 1966, is supported. Some details on important morphological characters of these species are provided.